A Retrospective Comparison between the PNST and other Paediatric Nutritional Screening Tools - Day, Andrew S.; Moeeni, Vesal; Walls, Tony (International Journal of Child Health and Nutrition, 2018)
Background: Although it is widely acknowledged that hospitalized children are at greater risk of malnutrition, the available paediatric Nutritional Risk Screening (NRS) tools have not yet become universally used to identify those children at greater risk. Furthermore, the utility of one NRS tool over another remains unclear. Materials and Methods: The utility of a recently developed tool, the Paediatric Nutritional Screening Tool (PNST), was evaluated using data previously collected in the assessment of three other NRS tools in 281 children from Iran and New Zealand. The sensitivity and specificity of each tool was then assessed based on the WHO criteria for malnutrition. Results: The PNST recognized about half of the malnourished patients while the other three tools identified at least 85% of these children. The sensitivity of PNST for moderate (BMI-z < 2) and severe malnutrition (BMI-z <-3) was 37% and 46% respectively, while the sensitivity for other three NRS tools ranged from 82-100%. Conclusion: In this data set, the PNST tool did not perform as well as the three more established NRS tools. Further work is required to provide optimal tools for the identification of hospitalized children at risk of malnutrition